The Synthetic β-Nitrostyrene Derivative CYT-Rx20 Inhibits Esophageal Tumor Growth and Metastasis via PI3K/AKT and STAT3 Pathways - Chiu, Wen-Chin; Lee, Yi-Chen; Su, Yu-Han; Wang, Yen-Yun; Tsai, Chun-Hao; Hou, Yi-An; Wang, Chie-Hong; Huang, Ying-Fong; Huang, Chih-Jen; Chou, Shah-Hwa; Hsieh, Pei-Wen; Yuan, Shyng-Shiou F. (PLOS ONE, 2016)
The β-nitrostyrene family have been implicated for anti-cancer property. However, the pharmacological role of β-nitrostyrene in esophageal cancer remain unclear. Here, a β-nitrostyrene derivative, CYT-Rx20, was synthesized and assessed for its anti-cancer activities and underlying mechanism in esophageal cancer. CYT-Rx20 induced cytotoxicity in esophageal cancer cells by promoting apoptosis through activation of caspase cascade and poly(ADP-ribose) polymerase (PARP) cleavage. Besides, CYT-Rx20 inhibited esophageal cancer cell migration and invasion by regulating the expression of epithelial to mesenchymal transition (EMT) markers. CYT-Rx20 decreased cell viability and migration through suppression of the PI3K/AKT and STAT3 pathways. Of note, the cytotoxicity and anti-migratory effect of CYT-Rx20 were enhanced by co-treatment with SC79 (AKT activator) or colivelin (STAT3 activator), suggesting the dependency of esophageal cancer cells on AKT and STAT3 for survival and migration, an oncogene addiction phenomenon. In xenograft tumor-bearing mice, CYT-Rx20 significantly reduced tumor growth of the implanted esophageal cancer cells accompanied by decreased Ki-67, phospho-AKT, and phospho-STAT3 expression. In orthotopic esophageal cancer mouse model, decreased tumor growth and lung metastasis with reduced Ki-67 and phospho-STAT3 expression were observed in mice treated with CYT-Rx20. Together, our results suggest that CYT-Rx20 is a potential β-nitrostyrene-based anticancer compound against the tumor growth and metastasis of esophageal cancer.